Dmitriy Dmitriyevich Yablokov (to the 110th anniversary) - Editorial Article (Бюллетень сибирской медицины, 2006)
In 2006 there is the 110th jubilee of D.D. Yablokov – phthisiatrician and pulmonologist, radiologist and pathologist, parasitologist and physician, rheumatologist and balneologist. He is one of the best representatives and followers of the traditions of Russian doctors. The biographic paper about D.D. Yablokov from the book Tomsk Dynasties. Twentieth Century (Tomsk, 1996) by the well-known journalist T.Yu. Kupert.